Emerging Therapeutic Potential of Mesenchymal Stem Cell-Derived Extracellular Vesicles in Chronic Respiratory Diseases: An Overview of Recent Progress - Ma, Yiming; Liu, Xiangming; Long, Yingjiao; Chen, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) are able to carry genetic and protein goods to mediate the interaction between MSCs and target cells. Recently, more and more researches have focused on the therapeutic role of MSC-EVs in chronic respiratory diseases. In this review, we summarize the cumulative strategies and mechanisms of MSC-EVs in treating chronic respiratory diseases. This review suggests that MSC-EVs may serve as a novel cell-free-based therapy for chronic respiratory diseases, including COPD, asthma, pulmonary fibrosis, and pulmonary arterial hypertension. In current studies of chronic respiratory diseases, umbilical cord and bone marrow are main sources of MSC-EVs, while adipose tissue, lung, and induced pluripotent stem cells are also applied. Isolation methods of MSC-EVs in treating chronic respiratory diseases involve ultracentrifugation, exosome extraction kits and anion-exchange chromatography. Intratracheal delivery and intravenous administration are the most widely used routes of MSC-EVs. MSC-EVs are able to transfer microRNAs and protein to target cells and further magnify the therapeutic effects.